Post-hospital falls incidence and risk factors among older adults: a systematic review and meta-analysis. (23rd October 2021) - Qian, Xing Xing; Chen, Zi; Fong, Daniel Y T; Ho, Mandy; Chau, Pui Hing
Abstract: Background: Post-hospital falls constitute a significant health concern for older adults who have been recently discharged from the hospital. Objectives: To systematically summarise existing evidence on the incidence and risk factors for post-hospital falls among older adults. Methods: A systematic review and meta-analysis was conducted. Six electronic databases were searched to identify cohort studies investigating the incidence and risk factors for post-hospital falls in older adults. The incidence and risk factors for post-hospital falls were extracted. The meta-analysis was used to calculate pooled incidences and 95% confidence intervals (CI). The meta-regression and subgroup meta-analysis were conducted to explore sources of heterogeneity in incidence proportions across the eligible studies. A qualitative synthesis was performed for the post-hospital falls risk factors. Results: Eighteen studies from eight countries ( n = 9, 080, 568) were included. The pooled incidence proportion of any and recurrent post-hospital falls was 14% (95% CI: 13%–15%) and 10% (95% CI: 5%–14%), respectively. Follow-up period, study quality, study country, setting, percentage of female subjects, percentage of subjects with previous falls and the primary data collection method for falls significantly contributed to the 64.8% of the heterogeneity in incidence proportions. Twenty-six risk factors for post-hospital falls were identified in the eligible studies, where biological factors were the most commonly identified factors. The highest risks were reported for previous falls, previous fractures, delirium and neurological diseases. Conclusion: The findings of this study suggested future post-hospital falls prevention should prioritise the needs of older adults with the dominant risk factors. Further investigations into the period-specific incidence and socioeconomic and environmental risk factors for post-hospital falls are also required.